Is there a China effect on the exports of East Asia emerging market economies to the US - Hooy, Chee Wooi; Baharumshah, Ahmad Zubaidi; Chan, Tze Haw (2010)
This paper analyze empirically whether the emergence of China as the world largest exporter in the last decade has affects export performance of the East Asia emerging market economies (EAEME), i.e. South Korea and ASEAN-5. These EAEME are heavily relying on their export to the western hemisphere, especially to the US, as a means for economy development. The emergence of China is expected to erode their US export. Augmented from standard trade model, we investigate the impact of China export as well as Renmimbi real exchange rates on EAEMEs’ US export. Using ARDL method, we find that only Philippines and Singapore show negative response to China trade effect, but the latter is not statistically significant. However, our further analysis with 5-year rolling estimates reveals that the crowding-out effect is obvious for almost all the EAEMEs and it is getting higher for South Korea, Philippines and Singapore. This is somewhat consistent with the view of Lall and Albaladejo (2004). For the Renmimbi effect, the ARDL estimates are positive significant and consistent with rolling estimates. We conclude that there is an increasing influence of Renmimbi on the export of EAEMEs to the US, especially after the de-pegging of the Renmimbi in July 2005.